A cell-surface phylome for African trypanosomes. - Andrew P Jackson; Harriet C Allison; J David Barry; Mark C Field; Christiane Hertz-Fowler; Matthew Berriman (Public Library of Science (PLoS), 2013)
The cell surface of Trypanosoma brucei, like many protistan blood parasites, is crucial for mediating host-parasite interactions and is instrumental to the initiation, maintenance and severity of infection. Previous comparisons with the related trypanosomatid parasites T. cruzi and Leishmania major suggest that the cell-surface proteome of T. brucei is largely taxon-specific. Here we compare genes predicted to encode cell surface proteins of T. brucei with those from two related African trypanosomes, T. congolense and T. vivax. We created a cell surface phylome (CSP) by estimating phylogenies for 79 gene families with putative surface functions to understand the more recent evolution of African trypanosome surface architecture. Our findings demonstrate that the transferrin receptor genes essential for bloodstream survival in T. brucei are conserved in T. congolense but absent from T. vivax and include an expanded gene family of insect stage-specific surface glycoproteins that includes many currently uncharacterized genes. We also identify species-specific features and innovations and confirm that these include most expression site-associated genes (ESAGs) in T. brucei, which are absent from T. congolense and T. vivax. The CSP presents the first global picture of the origins and dynamics of cell surface architecture in African trypanosomes, representing the principal differences in genomic repertoire between African trypanosome species and provides a basis from which to explore the developmental and pathological differences in surface architectures. All data can be accessed at: http://www.genedb.org/Page/trypanosoma_surface_phylome.